Death cases involving certain new psychoactive substances: A review of the literature. (May 2019) - Kraemer, Michael; Boehmer, Anna; Madea, Burkhard; Maas, Alexandra
Highlights: Summary of fatalities with findings of new psychoactive substances previously described in scientific literature. Overview of postmortem concentrations of new psychoactive substances determined in various biological matrices. The compiled data assist forensic toxicologists with the interpretation of death cases involving new psychoactive substances. Abstract: In the last decades, more and more new psychoactive substances (NPS) were introduced on the drug market which were sold as "legal" alternatives for classic drugs and misused medications. Due to an increased number of available substances and a growing utilization by users of common drugs but also by inexperienced users because of the supposed "legal" status, also undesired adverse effects of these NPS, at worst leading to death, became apparent. This review summarizes fatalities previously described in scientific literature which were attributed to the use of NPS or such cases, in which intake of NPS was proven or even assumed to contribute to death. This summary includes an overview of substances involved (particularly synthetic cannabinoids ("spice"), novel opioids and synthetic cathinones ("bath salts")) as well as of postmortem concentrations determined in various biological matrices. The compiled data assist forensic toxicologists with the interpretation of death cases involving NPS.